Potential of South African entomopathogenic nematodes to control the leaf miner, Holocacista capensis (Lepidoptera: Heliozelidae) - Steyn, L.A.I.; Addison, P.; Malan, A.P. (South African Journal of Enology and Viticulture, 2019)
The Cape grapevine leafminer, Holocacista capensis, a sporadic pest of economic importance, is found in South African table and wine grape vineyards. The cocoon casings, constructed by the final instar larvae, can be found attached to grape bunches, posing a phytosanitary risk for table grape export markets. The current study aimed to determine the susceptibility of leaf-mining H. capensis larvae to seven entomopathogenic nematode (EPN) species belonging to Steinernematidae and Heterorhabditidae. To determine nematode virulence occupied leaf-mining galleries were extracted from infested leaves and inoculated with 200 infective juveniles (IJs) in 50 μl of distilled water, for each of the EPNs screened. Concentration assays were conducted and and lethal dose was determined for the three most virulent species (Heterorhabditis baujardi, H. indica and H. noenieputensis), using concentrations of 0, 25, 50, 100, 200, and 400 IJs/leaf-mining larva. High mortality of leaf-mining larvae was obtained with H. baujardi (92%), H. noenieputensis (85%) and H. indica (83%). Almost double the number of H. noenieputensis (34 nematodes/insect) penetrated the insect larvae, in comparison with the other two EPNs. However, the relative potency of H. baujardi was 3.56 times higher than for H. indica, whilst that of H. indica was 2.57times higher than it was for H. noenieputensis. The results obtained in the laboratory were found to be encouraging, especially with regard to the nematodes’ ability to penetrate the leaf-mining galleries, and to infect the larvae successfully.